Somatic Hypermutation and Diverse Immunoglobulin Gene Usage in the Human Antibody Response to the Capsular Polysaccharide of Streptococcus pneumoniae Type 6B - Zhou, Jianhui (American Society for Microbiology, 2004)
Combinatorial cloning and expression library analysis were used to determine the expressed human antibody repertoire specific for the capsular polysaccharide (PS) of Streptococcus pneumoniae serotype 6B. Sequence analysis of 55 6B-specific antibody Fab fragments isolated from six vaccinated donors reveal that different individuals used a variety of heavy and light chain germ line variable (V) region genes to form pneumococcal capsular PS (PPS) 6B-specific paratopes. Within each donor, however, the response was more restricted, with five of the six donors using at most one or two gene pairs to form combining sites. Analysis also indicated that although the response in each donor was oligoclonal in terms of variable gene usage, the combination of extensive somatic hypermutation, deletion of germ line-encoded residues, insertion of non-germ line-encoded residues, and intraclonal isotype switching generated a surprising degree of paratope diversity within the individuals analyzed. In contrast to previously studied PS-specific responses, we find that the PPS 6B repertoire makes use of a diverse collection of heavy-chain and light-chain V region gene products to form specific paratopes, with no apparent tendency for conservation of immunoglobulin gene usage between individuals.